A study manual on the basics of financial management. - Mwisho, A. M (Research, Information and Publication Department, 2025)
I have written this students' manual titled "The Basics of Financial Management" after teaching financial management as a subject in the undergraduate and graduate programmes. It is to my opinion that readers, especially students who studies financial management as a subject may find this manual very helpful. I have used the simple English language to make it easier for the reader to understand faster. This manual has taken into consideration the financial management taught in both undergraduate and graduate programmes.